Bir iş yeri çalışanlarında yalnızlık, depresyon ve tükenmişliğin incelenmesi - Tüfekçi, Burcu (My University, 2018)
Giriş: Yetişkin bir insan günün önemli bir kısmını iş yerinde geçirmekte ve iş yaşamı ruh sağlığını, ruh sağlığı da iş yaşamını etkileyebilmektedir. Çalışanların yalnızlık, depresyon ve tükenmişlik açısından ele alınması toplum ruh sağlığı hizmet sunumu için önemli olabilecektir. Amaçlar: Bu çalışmanın amacı bir iş yeri çalışanlarında yalnızlık, depresyon ve tükenmişliğin incelenmesidir.Yöntem: Tanımlayıcı nitelikte olan araştırma, İstanbul'da bir iş yerinde yapılmıştır. Araştırmanın evrenini bir işyerinin çalışanları (N=450), örneklemini ise 265 çalışan oluşturmaktadır. Veriler, Kişisel Bilgi Formu, UCLA Yalnızlık Ölçeği 3. Versiyon, Maslach Tükenmişlik Envanteri ve Beck Depresyon Envanteri ile toplanmış, Shapiro-Wilk testi, Tek yönlü varyans analizi, Student’s t test, Kruskal Wallis test, Mann-Whitney U, Pearson ve Spearman korelasyon analizi ile değerlendirilmiştir.Bulgular: Katılımcıların yaş ortalaması 33.99±8.15 (min=21, max=65)’tir. Katılımcıların %78.9’u erkek, %51.7’si ilköğretim mezunu, %83’ü işçidir. Katılımcıların UCLA yalnızlık ölçeği puan ortalaması 39.83±8.98; BECK depresyon ölçeği puan ortalaması 8.06±7.66 ve Maslach Tükenmişlik Envanteri alt boyutlarından; duygusal tükenme 20.05±7.17, duyarsızlaşma 8.78±3.94, kişisel başarı puan ortalaması 27.90±6.26’dır. Sonuç: Bu araştırmanın bulguları, çalışanların yalnızlık puanlarının orta, depresyon puanlarının düşük düzeyde olduğunu yalnızlık, depresyon ve tükenmişlik puanları arasında anlamlı ilişkiler olduğunu gösternmektedir.

Introduction: A major part of an adult's day is spent in the workplace and working life can affect the individual's mental health while mental health in turn has an impact on working life. Assessing employees in terms of loneliness, depression and burnout can be an important factor in providing public health services. Aims: The aim of this study is to examine loneliness, depression and burnout in the employees of a workplace.Method: Of descriptive design, the study was conducted at a workplace in Istanbul. The universe of the study comprised the employees of the workplace (N=300); the sample consisted of 265 employees. The data were collected using the Personal In-formation Form, the UCLA Loneliness Scale (Version 3), the Maslach Burnout In-ventory and the Beck Depression Inventory, and were analyzed with the Shapiro-Wilk test, the one-way analysis of variance, the Student's t test, the Kruskal Wallis test, Mann-Whitney U and Pearson's and Spearman's correlation analyses.Results: The mean age of the participants was 33.99±8.15 (min=21, max=65) years. Of the participants, 78.9% were men, 51.7% were elementary school graduates and 83% were laborers. The UCLA loneliness scale mean score of the participants was 39.83±8.98; their BECK depression inventory mean score was 8.06±7.66 and out of the subdimensions of the Maslach Burnout Inventory, mean scores for emotional exhaustion were 20.05±7.17, 8.78±3.94 on the desensitization and 27.90±6.26 on the personal accomplishment subscales. Conclusion: The findings of our research reveal that employees' loneliness scores are average, their depression scores are at a low level and that there are significant relationships between loneliness, depression and burnout scores.
Keywords: Araştırma; Çalışanlar; depression and burnout; depresyon; Hemşirelik; Loneliness; Psikiyatri hemşireliği; Psikolojik yönler; tükenmişlik; Yalnızlık